Experimental Model of Hindlimb Suspension-Induced Skeletal Muscle Atrophy in Rodents - Marquez-Andrade, J (Humana Press Inc., 2019)
Due to the difficulty of performing research protocols that reproduce human skeletal muscle disuse conditions, an experimental animal model of “hindlimb suspension” (or hindlimb unloading) was developed. This method was created in the 1970s and utilizes rats and mice to mimic space flight and bed rest in humans. It provides an alternative to investigate mechanisms associated with skeletal muscle mass loss and interventions designed to attenuate atrophy induced by hindlimb unloading. The mentioned protocol also allows investigating quality of bones and changes in several physiological parameters such as blood pressure, heart rate, plasma or tissue lipid composition, and glycemia. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.